The use of Artificial Intelligence in enhancing Arabic Regional TV News Stations - Elzakazeky, Engy Mohamed (AUC Knowledge Fountain, 2026)
Arabic regional TV news stations have started using artificial intelligence (AI) as a tool for facilitating journalism work, coping with technology, and engaging audiences, as a result of the digital transformation in the television industry. This study examines how Arab regional TV news stations are incorporating AI into their operations, including its uses, opportunities, and limitations, in its early stages, through in-depth interviews with 14 media professionals in 13 Arab news stations. By reflecting on their own experiences, a purposive sample of news editors, managing editors, and graphic designers employed by news channels were interviewed. These media professionals were able to offer insights into the impact of AI usage in the television news stations. The participants shared their thoughts on the benefits and drawbacks of utilising AI in the television news stations. In order to provide participants with accessibility and flexibility, the interviews were conducted via Zoom meetings between February and August of 2025. In addition, the study explores how artificial intelligence applications are being integrated into newsroom workflows, including content production, research, and data analysis. By focusing on professionals’ perspectives, the research seeks to provide a clear understanding of how artificial intelligence is currently applied in television news environments. The study found that the majority of the interviewed professionals are using AI in systematic operations, not in creative issues, due to the AI limitations, including lack of accuracy, lack of emotions, and lack of creativity mainly. However, the majority of interviewees also concurred that while AI has become essential in facilitating work in news stations, it does not pose a threat to journalists and cannot take the position of actual human journalists. By focusing on professionals' perspectives in Arab news stations, the research examined AI utilization as a factor affecting audience engagement and viewership, especially among the new generations. Most interviewees said that AI is being integrated into the workflow, accordingly, the production cycle is expected to increase.